SWOT Analysis in Business Development at Property Company PT. XYZ - Azhari, Farhan (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2024)
SWOT analysis has become an important tool for identifying internal and external factors that influence company performance and strategy . The purpose of this research is to examine the use of analysis SWOT in business development at the real estate company PT .XYZ A qualitative approach is used to assess the strengths, weaknesses, opportunities and threats faced by PT . The analysis results show that PT XYZ has many key strengths, including a diversified real estate portfolio, strong reputation, and experienced management team However, there were weaknesses exposed, such as a reliance on real estate market cycles and a lack of presence in new markets.